International experience for laparoscopic major liver resection. (6th August 2014) - Dagher, Ibrahim; Gayet, Brice; Tzanis, Dimitrios; Tranchart, Hadrien; Fuks, David; Soubrane, Olivier; Han, Ho‐Seong; Kim, Ki‐Hun; Cherqui, Daniel; O'Rourke, Nicholas; Troisi, Roberto I.; Aldrighetti, Luca; et al.
Abstract Although minor laparoscopic liver resections (LLRs) appear as standardized procedures, major LLRs are still limited to few expert teams. The aim of this study was to report the combined data of 18 international centers performing major LLR. Variables evaluated were number and type of LLR, surgical indications, number of synchronous colorectal resections, details on technical points, conversion rates, operative time, blood loss and surgical margins. From 1996 to 2014, a total of 5388 LLR were carried out including 1184 major LLRs. The most frequent indication for laparoscopic right hepatectomy (LRH) was colorectal liver metastases (37.0%). Seven centers used hand assistance or hybrid approach selectively for LRH mostly at the beginning of their experience. Seven centers apply Pringle's maneuver routinely. The conversion rate for all major LLRs was 10% and mean operative time was 291 min. Mean estimated blood loss for all major LLR was 327 ml and negative surgical margin rate was 96.5%. Major LLRs still remain challenging procedures requiring important experience in both laparoscopy and liver surgery. Stimulating the younger generation to learn and accomplish these techniques is the better way to guarantee further development of this surgical field.